LEARNING GRAMMAR BY LYRIC OF ENGLISH SONGS AS EASY METHOD TO IMPROVE THE USE OF INTERNATIONAL LANGUAGE - Uswatun Hasanah (Proceedings Education and Language International Conference, 2017)
Grammar is rules for forming words and making sentences. It needs to use correctly in daily English speaking and academic writing. The use of grammar for non native English learner is quite difficult. They do not only need to memorize all the formulasbut also they have to apply grammar in their sentences. Therefore, there is one easy method for beginner to learn grammar by lyric of English Songs. This method works by analyzing each sentence in lyric of songs. It comes to be easy because learner can do their hobby in listening music while learning the English grammar. This paper will use library research to analyze deeply about improving ability in learning grammar by lyric of English Songs especially on verb tenses. There are many verb tenses analyzed in some lyric of English songs that will be discussed in this paper.Keywords: learning grammar, English song, easy method, international language